Impact of Relevance and Distraction on Driving Performance and Visual Attention in a Simulated Driving Environment. Issue 3 (13th March 2013) - Garrison, Teena M.; Williams, Carrick C.
Summary: Previous demonstrations of the impact of cellular phone conversations on visual attention when driving have primarily focused on attention to stimuli that are not relevant to driving. In contrast, we used a driving simulator and eye tracking to examine attention allocation across driving‐relevant and driving‐irrelevant items in the environment depending on whether drivers were distracted. Performance measures indicated that distraction negatively impacted vehicle control. However, driving relevance and the presence of distraction did not interact, suggesting that participants responded to potential hazards similarly in driving‐only and distraction conditions. In contrast, eye movement results indicated an interaction between distraction and relevance. Drivers attended more to driving‐relevant objects, and these objects showed smaller decrements in number of gazes in the distraction condition, compared with less relevant items. Even under distraction conditions, experienced drivers continued to attend to potential hazards, allocating less attention to billboards and roadway signage. Copyright © 2013 John Wiley & Sons, Ltd.